Analisis disposisi berpikir kritis matematis siswa dalam menyelesaikan soal relasi dan fungsi ditinjau dari kecemasan matematis - Risesti, Welny; Rahmatina, Desi; Izzati, Nur (Karoteh Utama, 2025)
Mathematical critical thinking disposition refers to students’ tendency to think logically, systematically, and deeply in evaluating statements or solving mathematical problems. On the other hand, students’ success in solving mathematical problems can be influenced by mathematical anxiety, which reflects the level of tension and emotional reactions to challenging mathematics learning situations. This study aims to describe students’ mathematical critical thinking disposition in solving problems related to relations and functions, viewed from the level of their mathematical anxiety. This descriptive qualitative research was conducted at SMA Negeri 7 Tanjungpinang. The research subjects consisted of two students from grade XI for each category of high, moderate, and low mathematical anxiety. The instruments used included a mathematical anxiety questionnaire, a mathematical critical thinking disposition test, and an interview guide. The results showed that students with high mathematical anxiety tended to have difficulty fulfilling the indicators of mathematical critical thinking disposition. The higher the level of mathematical anxiety, the lower the students’ ability in mathematical critical thinking. Meanwhile, students with moderate and low levels of mathematical anxiety demonstrated better and relatively similar dispositions of mathematical critical thinking. These findings indicate that the level of mathematical anxiety affects students’ mathematical critical thinking disposition.